Cervical Scoliosis: Clinical and Radiographic Outcomes. (February 2016) - Mesfin, Addisu; Bakhsh, Wajeeh R.; Chuntarapas, Tapanut; Riew, K. Daniel
Study Design: Retrospective study. Objective: Cervical scoliosis is a rare condition that can arise from various etiologies. Few reports on the surgical management of cervical scoliosis exist. Our objective was to evaluate clinical and radiographic outcomes following surgical management of cervical scoliosis. Methods: We evaluated our cervical spine surgical database for patients with cervical scoliosis (Cobb angle > 10 degrees) from 2005 to 2010. Demographic data including age, gender, diagnoses, and primary versus revision surgery was collected. Surgical data including procedure (anterior versus posterior), estimated blood loss (EBL), length of surgery, length of hospitalization, and complications was recorded. Preoperative and postoperative Cobb angle measurements and Neck Disability Index (NDI) scores were recorded. Results: Cervical scoliosis was identified in 18 patients. We excluded 5, leaving 5 men and 8 women with an average age of 50.7 (median 52, range 25 to 65). The average follow-up was 40 months (median 36.5, range 5 to 87). An anterior-only approach was used in 6 cases (average 4 levels fused), 5 cases were posterior-only approach (average 8.7 levels fused), and 2 cases were combined anterior-posterior approach. The EBL was an average of 286 mL (median 150, range 50 to 900), the average surgical time was 266 minutes (median 239, range 136 to 508), and the average hospital stay was 2.7 days (median 2, range 1 to 7). Complications occurred in 7 patients, and 2 developed adjacent segment pathology. The average coronal Cobb angle preoperatively was 35.1 degrees (median 31, range 13 to 63) and corrected was 15.7 degrees (median 10.5, range 2 to 59) postoperatively ( p < 0.005). The average NDI preoperatively was 24.9 (median 26, range 6 to 37) and was reduced to 17.8 (median 18, range 7 to 30) postoperatively ( p < 0.02). Conclusion: Surgical management of cervical scoliosis can result in deformity correction and improvement in patient outcomes. Higher rates of complications may be encountered.